Dementia and the Over-75 Check: the role of the primary care nurse. - Trickey, H; Turton, P; Harvey, I; Wilcock, G; Sharp, D (2000)
Primary care nurses are very likely to provide a substantial part of the routine care for patients with dementia. In order to examine the knowledge and attitudes of the primary care nurses who undertake the Over-75 Check, towards assessing and managing patients with symptoms of dementia, and to assess their level of support for a clinical practice guideline, a postal questionnaire survey was undertaken of primary care nurses responsible for the Over-75 Check in 209 general practices in Gloucester, Avon and Somerset. The questionnaire ascertained some demographic information about the nurses, their training and the practice routine for the Over-75 Check. It also included a case vignette describing a typical presentation of dementia at an Over-75 Check. A 65% response rate was achieved. Only one-fifth of respondents ever used formal validated cognitive tests as part of the Over-75 Check. In response to the vignette, nearly 10% took no action at all and a further 25% simply referred the patient on. Amongst the remainder there was considerable variation regarding the tasks considered to be within their remit. The respondents strongly supported the introduction of guidelines. Given the variation in professional responsibilities between practices, it is proposed that a clinical practice guideline covering diagnosis, assessment and management of dementia should address the practice as a whole rather than be targeted to specific professionals. The guideline should prompt professionals carrying out an Over-75 Check to recognize symptoms of dementia and raise awareness of the range of tasks which need to be undertaken in confirming diagnosis, assessing needs and managing patients. Results from this study suggest that improved training and increased autonomy for primary care nurses would improve access to services for these patients and their carers.